An Analysis of the Factors Deterring the Students from Participating in Exchange Programs at Tishk International University. - Aws Y. Abed; Zainab A. Alani (Eurasian Journal of Management & Social Sciences)
This study aims to check the attitudes of Tishk International University (TIU) students towards student exchange programs in terms of awareness, tendency, and challenges related to it. The study used an online questionnaire survey and the sample consisted of 150 students of Business faculty but only 100 valid responses were collected. The main findings of this study indicate an awareness and interest in student exchange programs, but the students are not seriously considering participating in such programs. The main channel for their information is the word of mouth and the university employees. The study also found that the main factors limiting student participation were the language and that they prefer to do a full degree abroad after finishing their study and not the one-semester study that TIU provides. Oddly, the visa was not reported as an issue. Furthermore, the results were discussed and translated into recommendations for the university and paved the way for future studies on this topic.